FROM THE VIEW OF THE COMMUNIST PARTY OF VIETNAM TO THE PRACTICE OF BUILDING SOCIAL SECURITY IN DANANG - Lê Đức Thọ (Tạp chí Khoa học Đại học Đà Lạt)
Ensuring social security has become a central issue in national development strategies, as the care and improvement of the material and spiritual life for our people is the highest objective of the construction cause of the Socialist society in Vietnam. And now we are striving for a social security system that will cover the entire population by 2020. This article analyzes the views of the Communist Party of Vietnam on social security implementation in the current period; Analyzes the situation of social security in Danang and thereby suggests some solutions to improve social security for people in Danang city today.